Discourse rules: the effects of clause order principles on the reading process. Issue 10 (26th November 2022) - Scholman, Merel C. J.; Blything, Liam; Cain, Kate; Hoek, Jet; Evers-Vermeul, Jacqueline
ABSTRACT: In an eye-tracking-while-reading study, we investigated adult monolinguals' ( N = 80) processing of two-clause sentences embedded in short narratives. Three principles theorised to guide comprehension of complex sentences were contrasted: one operating at the clause level, namely clause structure (main clause – subordinate clause or vice versa), and two operating at the discourse-level, namely givenness (given-new vs. new-given) and event order (chronological vs. reverse order). The results indicate that clause structure mainly affects early stages of processing, whereas the two principles operating at the discourse level are more important during later stages and for reading times of the entire sentence. Event order was found to operate relatively independently of the other principles. Givenness was found to overrule clause structure, a phenomenon that can be related to the grounding function of preposed subordinate clauses. We propose a new principle to reflect this interaction effect: the grounding principle.